Argentina, homes in Ushuaia near Martial Mountains - Forman, Harrison, 1904-1978 (1954)
Ushuaia - Southernmost town in world at stinger-tip of S. [South] America. It's 60 miles from Cape Horn, 450 miles from Antarctica. Color Box 7